(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
Within the framework of the Nicaraguan revolution, a small group of internationalist militants organized to collaborate with the triumph of the insurrectionary movement, its name was Brigade Simón Bolívar. After the fall of Anastasio Somoza, and once the government of the Sandinista National Liberation Front (FSLN) was installed, the brigade had a short but intense political life. In this sense, the text addresses its ideological origin, its organizational development, as well as the place that has had its formation and expulsion from the Central American country within specialized literature.